Penilaian Kinerja Keuangan Berdasarkan Metode Market Value Added (MVA) pada PT Kimia Farma (Persero) Tbk - Arlina Pratiwi Purba (Economics, Business and Management Science Journal, 2023)
This final report is entitled "Financial Performance Assessment Based on the Market Value Added (MVA) Method at PT Kimia Farma (Persero) Tbk for the 2018-2021 Period". The purpose of this final report is to determine the financial performance of PT Kimia Farma (Persero) Tbk in terms of the financial statements using the Market Value Added (MVA) method. The data used is secondary data obtained through the official website of PT Kimia Farma (Persero) Tbk and analyzed using the Market Value Added (MVA) method. The results of the final report show that the MVA of PT Kimia Farma (Persero) Tbk in 2018, 2020 and 2021 is positive, meaning that the performance of the management of PT Kimia Farma (Persero) Tbk is successful in maximizing investor wealth while 2019 is negative, meaning that the performance of the management of PT Kimia Farma (Persero) Tbk has not been successful in maximizing investor wealth.